Synergizing Sulfonated Hydrothermal Carbon and Microwave Irradiation for Intensified Esterification Reaction - Tumkot, Laddawan (ACS Omega, 2020)
[Image: see text] The synergy of sulfonated hydrothermal carbon and microwave (MW) irradiation was applied for the esterification of oleic acid with methanol (MeOH) to produce biodiesel. The effects of temperature, reaction time, ratio of oleic acid to methanol, and catalyst loading were investigated at a fixed MW power of 400 W. The addition of hexane, serving as a co-solvent and separator, was also investigated. The optimum conditions for the proposed process were oleic acid-to-methanol molar ratio of 1:5 and hexane-to-methanol ratio of 0.5 (v/v) in the presence of a 5 wt % catalyst, at 100 °C for 60 min, obtaining a 97% yield of oleic acid methyl ester. The addition of slight amounts of hexane resulted into an eightfold reduction in the amount of MeOH needed to obtain a yield above 90%, which normally required a MeOH-to-oil ratio of 40:1. This proposed novel approach could provide a more cost-effective method for the esterification of oil to produce biodiesel, that is, reactive separation utilizing carbon-based catalysts under MW irradiation.